Effectiveness of Upright Position and Sim Position on Acceleration of Active Phase of First Stage Labor - Pane, Herviza Wulandary; Armaya, Rina; Joharmi, Joharmi (Journal of Language and Health, 2024)
Labor in a woman begins when the uterus experiences contractions with increasing intensity. One of the easy preventive measures is mobilization during labor with upright position and sim position. The purpose of this study was to determine the effectiveness of upright position and sim position to overcome accelerated labor in the first stage at the Rahmawati clinic in 2024. This type of research uses the Quasy Experimental method with One Group Pre-test Post-test. The population in this study were all mothers giving birth at the Rahmawati Clinic. The sample taken was all mothers giving birth who came to the Rahmawati clinic totaling 30 people. The sampling technique used accidental sampling. Measurement of the length of the first stage uses the duration of minutes since the mother giving birth was diagnosed with active phase I labor. Data analysis used the Wilcoxont ​​test. The results of the study conducted on 30 mothers giving birth showed a significant change in the acceleration of active phase I labor after the intervention was carried out. Before the intervention, only 9 out of 30 mothers gave birth experienced rapid labor, while the other 21 mothers experienced slower labor. However, after the intervention, the number of mothers who experienced rapid labor increased drastically to 28 out of 30, while only 2 mothers still experienced slow labor. The results of the statistical test showed a Z value of -4.359, which indicated a significant difference between the conditions before and after the intervention. The p-value of 0.000 (p <0.05) indicates that this result is very statistically significant, so there is a difference in the acceleration of active phase I labor before and after using the upright position and sim position.